Genetic Analysis of Turkish lynx (Lynx lynx) Based on Mitochondrial DNA Sequences - Keten, A.; TEZ, COŞKUN; İBİŞ, OSMAN; ÖZCAN, SERVET; Kirmanoglu, C. (Russian Journal of Genetics, 2019)
Genetic variability and phylogenetic relationships of the Eurasian lynx (Lynx lynx) have been reported by various researchers from species' range. As genetic data of Turkish lynx comes from a single genetic study that only contains limited number of lynx samples from the Anatolian part of Turkey, there is still a lack of genetic information for the Eurasian lynx population distributed in Turkey. In this study, mitochondrial Cyt b (1140 bp) and COI (630 bp) sequences were obtained from eight Anatolian samples of the Eurasian lynx. The Anatolian lynx sequences were compared to those of conspecific populations published in GenBank. We found two COI (630 bp) and four Cyt b (1140 bp) haplotypes among the eight Anatolian lynx sequences. Despite the limited number of the Anatolian lynx sequences, Bayesian, Maximum Likelihood, Neighbor-Joining and Network analyses revealed that there was a significant genetic differentiation in the Eurasian lynx, in that at least there were two main mitochondrial lineages within the sampling area. Also, the present study suggested that the Anatolian lynx might have a relatively high genetic variability despite the scarce samples.